Molecular and Clinicopathologic Heterogeneity of Intracranial Tumors Mimicking Extraskeletal Myxoid Chondrosarcoma. Issue 8 (18th June 2018) - Velz, Julia; Agaimy, Abbas; Frontzek, Karl; Neidert, Marian Christoph; Bozinov, Oliver; Wagner, Ulrich; Fritz, Christine; Coras, Roland; Hofer, Silvia; Bode-Lesniewska, Beata; Rushing, Elisabeth
Abstract: Primary intracranial neoplasms with features of extraskeletal myxoid chondrosarcomas (EMC) are extremely rare and poorly characterized tumors with only ∼12 cases described, the majority lacking molecular confirmation. There is an urgent need for the integration of molecular studies for correct subclassification of these tumors in order to predict clinical behavior, guide therapeutic decision-making, and provide novel targets for therapy. Clinical and pathologic data of 3 intracranial EMC-like myxoid neoplasms were retrospectively reviewed. In 2/3 cases, immunohistochemistry showed loss of nuclear SWI/SNF-related matrix-associated actin-dependent regulator of chromatin subfamily B member 1 (SMARCB1; integrase interactor 1 [INI1]) staining accompanied by monosomy of chromosome 22q (fluorescence in situ hybridization [FISH]). These 2 cases had no evidence of any fusion products by next generation sequencing (NGS). The third case had intact SMARCB1 expression and showed instead a rearrangement of the EWSR1 gene detected by FISH, with an EWSR1-CREB1 gene fusion on NGS. None of the cases showed rearrangement of the NR4A3 gene, neither by FISH nor by NGS. This small case series highlights the molecular heterogeneity of intracranial neoplasms in the morphologic spectrum of EMC. Distinct molecular alterations found in tumors with morphologic features of EMC encompass SMARCB1(INI1) loss and EWSR1-CREB gene fusions. None of the cases showed rearrangements of NR4A3 genes, suggesting they are distinct from conventional EMC.